الدور الاجتماعي لجوانب من الأحباس بالغرب الإسلامي ما بين القرون 4-9هـ. = 10-15م. من خلال المصادر الفقهية والنوازل - همر، محمد ولد; البشير، غانية (جامعة وهران 1 أحمد بن بلة - مختبر تاريخ الجزائر, 2021)
Works of jurisprudence issues are crucial resources for the study of different life aspects in the Islamic west, especially socioeconomic aspects that enabled these fatwas to track them accurately and neutrally. The issues of hubous (Awqaf/ mortmain property) is filled with property cases held by public and private sectors. It abounds with many waqf documents indicating the prevalence of the phenomenon of hubous in the Islamic West. Moreover, it conspicuously demonstrates the mortmain property samples, their dimensions, limits, and the methods of their exploitation. These documents were recorded in the Nawazili fatwas compilations highlighted the duration of the leasing, cultivation, and farming operations in relation to agricultural lands, in addition to jurists’ opinions on selling the rubble of hubous and replacing them in case of chaos and impossibility of benefit. This research briefly deals with the role of hubous in the economic, religious, cultural and scientific aspects, and more particularly its social role. We highlighted the role of hubous in preserving money from the confiscations of rulers and revolutionaries, as well as providing dignified life and economic well-being to that holding the mortmain property, whether they are close relatives or far. Additionally, we highlighted the role of hubous insocial solidarity, festivals, and religious occasions, and showed the different types of hubous. Where we have listed examples of hermitage real estate such as houses, hotels, and agricultural lands, as well as transferred custody.
تشكل المصادر الفقهيه والنوازل مصادر هامة لدراسة مختلف جوانب الحياة في الغرب الإسلامي، لا سيما الجوانب الاجتماعية والاقتصادية التي يمكن تتبع مختلف حيثياتها بشكل يتسم بالدقة والحياد من خلال هذه المصنفات، وتعد نوازل الأحباس سجلا حافلا بقضايا الممتلكات الموقوفة من طرف العامة والخاصة، إذ تزخر بالعديد من الوثائق الوقفية الدالة على شيوع ظاهرة الأحباس والحرص عليها في بلاد الغرب الإسلامي وتبين بجلاء العينات الموقوفة وأبعادها وحدودها وطرق استغلالها، حيث أبرزت هذه الوثائق المدونة في مصنفات الفتاوى مدة تأجير الأحباس وعمليات المزارعة والمساقاة بالنسبة للأراض الزراعية، وآراء الفقهاء في بيع أنقاض الحبس واستبداله في حالة الخراب وتعذر الاستفادة منه. وقد تم التطرق في هذا البحث بشكل مقتضب إلى دور هذه الأحباس في الجانب الاقتصادي والديني والثقافي والعلمي، وتم بإسهاب الحديث عن دورها الاجتماعي، إذ أبرزنا دور الأحباس في حفظ أموال المحبس من مصادرات الحكام والثائرين وتوفير حياة كريمة ورفاه اقتصادي للمحبس عليهم، سواء كانوا لصيقي القرابة بالمحبس كأبنائه ونسائه أو بعيدين منه، كما أبرزنا دورها في التكافل الاجتماعي والمناسبات الدينية وبينا مختلف أنواعها، حيث أوردنا نماذج من العقارات المحبسة كالدور والفنادق والأراض الزراعية وكذلك الأحباس المنقولة.
Keywords: الظواهر الطبيعية -- الاحباس -- التكافل الإجتماعي -- الدراسات التاريخية